Transgender Women Have Higher Human Papillomavirus Prevalence Than Men Who Have Sex With Men—Two U.S. Cities, 2012–2014 - Singh, Vidisha (Sex Transm Dis, 2019)
BACKGROUND: Human papillomavirus (HPV) prevalence is high among men who have sex with men (MSM), yet little is known about HPV among transgender women (TGW). We assessed HPV prevalence and knowledge among TGW compared with MSM. METHODS: We enrolled TGW and MSM aged 18 to 26 years from clinics in Chicago and Los Angeles during 2012 to 2014. Participants self-reported gender identity, HIV status, HPV knowledge, and vaccination status. Self-collected anal and oral specimens were tested for HPV DNA (37 types); serum was tested for HPV antibodies (4 vaccine types). Prevalence among unvaccinated TGW and MSM was compared using prevalence ratios (PRs) and 95% confidence intervals (CIs). Participants without DNA or serologic evidence of HPV were considered naïve. RESULTS: Among 1033 participants, 49 were TGW. Among 44 TGW and 855 MSM who were unvaccinated, any HPV DNA was detected in anal specimens from 39 (88.6%) TGW and 606 (70.9%) MSM (PR, 1.3; 95% CI, 1.1–1.4), and oral specimens from 4 (9.1%) TGW and 81 (9.5%) MSM (PR, 1.0; 95% CI, 0.4–2.5). Antibodies were detected among 37 (84.1%) TGW and 467 (54.6%) MSM (PR, 1.5; 95% CI, 1.3–1.8). Most participants were naïve to 1 or more HPV vaccine type/s, including 29 (65.9%) TGW and 775 (90.6%) MSM (PR, 0.7; 95% CI, 0.6–0.9). Most TGW (55.1%) had never heard of HPV vaccine. CONCLUSIONS: Among TGW, HPV prevalence was high and knowledge was low. Most were still naïve to 1 or more HPV vaccine type. Although vaccination ideally occurs prior to exposure, findings support existing national recommendations to vaccinate TGW and MSM, and suggest additional outreach might increase vaccination.